Can We Eliminate Opioids After Anterior Cruciate Ligament Reconstruction? A Prospective, Randomized Controlled Trial. Issue 14 (December 2021) - Moutzouros, Vasilios; Jildeh, Toufic R.; Tramer, Joseph S.; Meta, Fabien; Kuhlmann, Noah; Cross, Austin; Okoroha, Kelechi R.
Background: Multimodal pain protocols have been effective for postsurgical pain control; however, no published protocol has been effective in eliminating opioid consumption. Purpose: To compare a multimodal nonopioid pain protocol versus traditional opioid medication for postoperative pain control in patients undergoing anterior cruciate ligament reconstruction (ACLR). Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 90 patients undergoing primary ACLR were assessed for participation. We performed a prospective, randomized controlled trial in accordance with the CONSORT (Consolidated Standards of Reporting Trials) 2010 statement. The study arms were a multimodal nonopioid analgesic protocol (acetaminophen, ketorolac, diazepam, gabapentin, and meloxicam) and a standard opioid regimen (hydrocodone-acetaminophen), and the primary outcome was postoperative visual analog scale (VAS) pain scores for 10 days. Secondary outcomes included patient-reported outcomes, complications, and satisfaction. The observers were blinded, and the patients were not blinded to the intervention. Results: A total of 9 patients did not meet inclusion criteria, and 19 patients declined participation. Thus, 62 patients were analyzed, with 28 patients randomized to the opioid group and 34 to the multimodal nonopioid group. Patients receiving the multimodal nonopioid pain regimen demonstrated significantly lower VAS scores compared with patients who received opioid pain medication ( P < .05). Patients were administered the Patient-Reported Outcomes Measurement and Information System Pain Interference Short Form, and no significant difference was found in patients' preoperative scores (opioid group, 58.6 ± 7.9; multimodal nonopioid group, 57.5 ± 7.4; P = .385) and 1-week postoperative scores (opioid group, 66.3 ± 8.2; multimodal nonopioid group, 61.4 ± 8.8; P = .147). When we adjusted for possible confounders (age, sex, body mass index, graft type), no significant differences in pain control were found between the 2 groups. The most common adverse effects for both groups were drowsiness and constipation, with no difference between the groups. All patients in the multimodal nonopioid group reported satisfactory pain management. Conclusions: A multimodal nonopioid pain protocol provided at least equivalent pain control compared with traditional opioid analgesics in patients undergoing ACLR. Minimal side effects, which did not differ between groups, were noted, and all patients reported satisfaction with their pain management.